DNS of turbulent heat transfer in pulsating channel flow - Tatsuro YAMAZAKI; Yutaka ODA; Ryosuke MATSUMOTO; Masashi KATSUKI (Nihon Kikai Gakkai ronbunshu, 2020)
A pulsating turbulent channel flow at constant wall temperature difference condition is studied by direct numerical simulation (DNS) to clarify the effect of pulsation frequency on turbulence statistics and heat transfer. The flow pulsation was forced to a turbulent channel flow by sinusoidal variation of pressure gradient. Four pulsation frequencies were tested for Womersley number, Wo = 19.8, 28.0, 39.6 and 56.0 at steady-state friction Reynolds number, Reτs = 300. Phase-averaged friction velocity and Nusselt number change periodically, showing different amplitude and phase lag to bulk Reynolds number, depending on Womersley number. Consequently, it is found that the time-local dissimilarity between momentum and heat transfer occurs due to the flow pulsation. Also, the phase-averaged streamwise velocity and turbulent kinetic energy can be scaled with phase-averaged friction velocity at low Womersley number. On the other hand, at high Womersley number, the phase-averaged turbulent kinetic energy is scaled with the time-averaged friction velocity. This fact implies that near-wall turbulent eddy structure changes following bulk Reynolds number variation at low frequency, but it cannot follow the rapid variation at high frequency and ends up holding near steady-state structure. This view is supported by the behavior of vortex structures which virtually does not change during one cycle at high Womersley number.